Fiscal policy and the employment problem in less developed countries - Peacock, Alan T.; Shaw, G. K. ([Paris] Development Centre of the Organisation for Economic Co-operation and Development, 1971)
A brief synopsis of the analysis on employment creation, and describe the policy environment in which fiscal measure are used.
Includes bibliographical references.
sju 22/01/2019
Loans
Keywords: Full employment policies; Fiscal policy